2005
DOI: 10.1007/s00436-005-0073-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a liposomal formulation of ivermectin in rabbit after a single subcutaneous administration

Abstract: Ivermectin is a member of the macrocyclic lactone family widely used in livestock, pets, and humans as a potent parasiticide. Slight differences in formulation may change the plasma kinetics and efficacy of these compounds. The aim of the study is to evaluate the ability of a liposomal formulation of ivermectin to generate an efficient exposure of the animal to the drug. Ten rabbits were subcutaneously administered with 0.3 mg kg(-1) of ivermectin using Ivomec (n=5) or a liposomal formulation (n=5). The areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
0
19
2
1
Order By: Relevance
“…6, 13 The results of the present study differ from those previously reported for IVM in rabbits. 6 In the previous study IVM was administered at 0.4 mg/kg whereas in this study it was administered at 0.3 mg/kg.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…6, 13 The results of the present study differ from those previously reported for IVM in rabbits. 6 In the previous study IVM was administered at 0.4 mg/kg whereas in this study it was administered at 0.3 mg/kg.…”
Section: Discussioncontrasting
confidence: 99%
“…20 In a previous study, the effect of lipid ingestion on the kinetic disposition of MXD has been investigated in rabbits following oral administration at a dose rate of 0.3 mg/kg. 13 This study suggested that lipid administration increases the systemic availability of oral MXD. However, the plasma availability of MXD after oral administration in the previous study was much lower (C max : 7.44 ng/mL, Previous studies have shown that the plasma disposition of endectocides in different animal species is significantly affected by the solvent vehicle of the drug formulation.…”
Section: Discussionmentioning
confidence: 93%
“…This suggested that SPC-SDC-MMs containing IVM could reach the bloodstream by the lymphatic pathway, which depended on the lymph node chains that absorbed the drug from the injection site. Also, the IVM injection demonstrated a slow and prolonged process of absorption due to the precipitation of the drug at the site of injection (Bassissi et al, 2006). Despite the difference in the absorption process, the two formulations shared similar pharmacokinetic profiles in rabbits.…”
Section: Discussionmentioning
confidence: 98%
“…One of the main goals of modern antiparasite chemotherapy is to optimize drugs to the pathogen and minimize side effects by innovative formulations to enhance the antihelmintic efficacy (Bassissi et al, 2006). Studies showed that the PC-BC-MMs system had great potential to improve the solubility of poorly soluble drug, particularly the lipophilic drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation